"Am I a snob?": modernism and the novel - Latham, Sean (Cornell University Press, 2003)
Is there a "great divide" between highbrow and mass cultures? Are modernist novels for, by, and about snobs? What might Lord Peter Wimsey, Mrs. Dalloway, and Stephen Dedalus have to say to one another? Sean Latham's appealingly written book Am I a.